Tahapan Kemunculan Gerakan Sosial Penolakan Tambang di Konawe Kepulauan - Mardiana, Wa Ode Sitti; Susetiawan, Susetiawan; Ikram, Mulkhaeri (Indo-MathEdu Intellectuals Journal, 2025)
This study discusses the form of the initial emergence of social movements carried out by the community in order to reject mining activities in the Konawe Islands region. The community carried out various forms of action as a form of rejection of government policies that were considered detrimental. Through the unification of forces in an organization called the Southeast Sulawesi People's Front Bela Wawonii (FRSBW), the community has a forum to voice their aspirations and concerns about the potential negative impacts of the presence of mining companies. This study uses social movement analysis according to Macionis, which groups social movements into three stages: the initial stage (emergence), the consolidation stage (coalescence), and the goal achievement stage. The research approach used is qualitative, with data collection techniques through field observations of community resistance actions against the entry of mining activities on Wawonii Island. Data analysis is conducted qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The research findings indicate that the emergence of this movement is born from the public's concerns and various issues circulating regarding the threats posed by mining activities, especially since Wawonii Island is categorized as a small island that is vulnerable to the dangers of mining impacts.